Theoretical study of the decomposition mechanism of a novel eco-friendly insulation medium HFO-1336mzz(E) considering the effect of trace humidity. (21st October 2021) - Liu, Jie; Wang, Feng; Zhong, Lipeng; Gan, Hui; Hai, Bin; Tang, Nian; Li, Li; Zhou, Yongyan
Abstract: As a strong greenhouse gas, sulfur hexafluoride used in electrical equipment has been advocated to be replaced. HFO-1336mzz(E), an eco-friendly insulation alternative medium with excellent insulation performance and environmental effect, deserves studied deeply. In this paper, the decomposition mechanism of HFO-1336mzz(E) is studied by density functional theory calculations. The effect of trace water on the decomposition properties is also considered and studied. Besides, multiple linear regression models are used to assess the insulation properties of main decomposition products that came from HFO-1336mzz(E). The results show that more than 15 molecules are formed in the decomposition process of HFO-1336mzz(E), among which CF3 CH=C=CF2, CF2 =CF–CH=CF2, C2 F6, and HF are the most abundant products. Besides, C2 F4, CF2 =CFH, and C2 H2 could be taken as typical products for diagnosing the serve fault degree that occurred in the electrical equipment. In terms of insulation properties, CF3 CH=C=CF2 and CF2 =CF–CH=CF2, two of the main products, with big volumes have excellent insulation strength that is slightly less than that of HFO-1336mzz(E). Small molecules with low dielectric strength such as CF3 H, CF3 OH, COF2, and HF, etc can also be produced in the presence of micro humidity. Luckily, the yield of these small molecules is small so that they will not have a significant impact on the insulation properties of the overall system. Remarkably, the presence of micro humidity will make it easier to generate toxic gas products such as COF2 and HF. Given these conditions, the acceptable moisture content in the power equipment is expected to propose before any application in the electrical industry. Relative studies on the decomposition mechanism of HFO-1336mzz(E)/H2 O in this paper may be helpful to understand the subsequent scientific experimental research.